(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2026)
This study analyzes financial education in Argentina and the population’s level of financial knowledge between 2022 and 2025, focusing on young people, a vulnerable group due to the limited preparation they receive in school. Also, it explores the role that financial education plays in everyday decision-making, its direct impact on both individual and collective well-being, and the consequences of its absence. Moreover, it examines the current place of these topics within the national educational curriculum and different approaches for incorporating them into schools. The goal is to ensure that young people acquire the necessary tools to manage their money in a responsible way. In conclusion, the Argentine population shows low levels of financial knowledge, highlighting the need to strengthen this area through concrete and effective government actions.